DETERMINASI SOSIAL LINGKUNGAN KERJA DAN EPIDEMIOLOGI MANAJERIAL: TINJAUAN LITERATUR DAMPAK PENGEMBANGAN KARIR DAN WORK-LIFE BALANCE TERHADAP KINERJA KARYAWAN MELALUI MEDIASI KEPUASAN KERJA DI RSUD PROVINSI NTB - Wahyu Nur Chalamsah Setiawan; Yuly Peristiowati (Bajang Institute, 2026)
Background: Employee performance in the healthcare sector results from complex interactions between organizational and individual factors. RSUD Provinsi NTB, as a public service center, faces challenges in maintaining productivity amidst high workloads. A managerial epidemiology approach and the social determinants of the work environment are crucial for systematically analyzing performance issues. Objective: This study aims to analyze the impact of career development and work-life balance on employee performance, with job satisfaction as a mediating variable, through a comprehensive literature review. Methods: This study employs a Systematic Literature Review (SLR) method. The literature search was conducted across Scopus, Google Scholar, and ScienceDirect databases covering the period 2016-2026. Inclusion criteria focused on original research articles discussing the relationships between variables within healthcare service organizations. Results: Findings indicate that career development and work-life balance significantly influence performance by enhancing job satisfaction. Job satisfaction is proven to be a key mediator; stagnant career policies and poor work-life balance are identified as organizational “risk factors” that diminish work output. Conclusion: The integration of transparent career policies and work-life balance support is essential for optimizing performance at RSUD Provinsi NTB. A managerial epidemiology approach provides a preventive framework for management in human resource administration.